Exchange Rate Expectations and the Current Exchange Rate: A Test of the Monetarist Approach - Somanath, V. S. (Journal of International Business Studies, 1984)
The monetarist model of the exchange rate includes expectations of the future exchange rate as a determinant of the current exchange rate. This paper investigates whether expectations are a significant determinant of the exchange rate. An expectations process that is consistent with a basic monetarist exchange rate model is considered. Alternative measures of expectations are generated using this process. In the empirical tests, while the standard forward exchange premium measure of expectations is statistically insignificant, some of the alternative measures are observed to be statistically significant.